Toxicological potential and chemical and phytochemical characterization of garcínia cambogia. (Research, Society and Development, 2020)
The use of medicinal plants for the treatment, cure and prevention of the disease is an ancient practice of mankind. Among the current ones, obesity is highlighted as a global public health problem in developed and developing countries. The study aims to outline the toxicological potential, as well as to evaluate the physicochemical and phytochemical characterization of Garcínia cambogia, in order to contribute to the safe use of this plant. They were hemoenergetic, phytochemical and toxicological, aiming to characterize the quality and safety of extracts obtained from Garcínia cambogia. It was observed that the content of foreign material, pH, total ash and acid insoluble ash were within the established limits. The values for humidity were higher than allowed. Phytochemical screening showed negative results for flavonoids and tannins, and a positive result for saponins. For the in vivo acute toxicity test the extract was categorized as "category 5" (2000 to 2500 mg / kg), and the acute lethal toxicity – LD50% estimated at 2500 mg / kg, was considered to be non-toxic. In the evaluation of the systemic toxicity no significant differences were observed between the animals of the test group and those of the control group. No macroscopic changes were observed in the organs after 14 days of experiment, demonstrating absence of acute toxicity. With the results obtained it was possible to contribute to a more detailed knowledge of Garcínia cambogia, with the more detailed information of its toxicological potential.